INNOVATIVE STRATEGIES FOR VOCABULARY ACQUISITION IN PERSIAN LANGUAGE LEARNING - Erkinxonova Azizaxon (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This research explores effective and innovative methods for acquiring vocabulary in Persian as a foreign language. It compares traditional memorization with modern tools such as mobile apps, spaced repetition systems, and context-based learning. The study involved surveying university students and showed that learners using digital tools and contextual learning retained vocabulary more effectively. The findings emphasize that blended strategies improve long-term retention and learner motivation.